Outcome of posterior lumbar interbody fusion in low-grade spondylolisthesis - Nimmagadda, Vamshikrishna Chand; Seenappa, Hiranya Kumar; Mittemari, Karthik Narayanamurthy; Paidipati, Rajashree (International Journal of Research in Orthopaedics, 2021)
Background: Spondylolisthesis is the slippage of all or part of one vertebra in relationship to a caudal vertebra, most commonly occurring in the lumbar spine. Fusion is the recommended treatment of choice. Posterior stabilization with posterior lumbar interbody fusion (PLIF) is an established procedure with good outcomes. To study functional and radiological outcomes of PLIF in grade 1 and 2 lumbar spondylolisthesis. Methods: This is a prospective study in 30 patients who underwent PLIF and followed up for one year. Functional outcomes were measured in terms of visual analogue scale (VAS) and the Modified Oswestry Disability Index (ODI), and the fusion was assessed on plain radiographs. Results: There was a significant improvement in VAS of low back pain (90.71%, p<0.001) and VAS of radiating (82.52%; p<0.001). The ODI scores were significantly improved (63.65%, p<0.001) at 1 year follow up. The fusion rate was 70%, and 56.66% patients reported excellent outcomes. Conclusions: Based on functional outcomes and the fusion rates of PLIF, we conclude that PLIF is a recommended and excellent surgical option in the management of low grade lumbar spondylolisthesis.